Building a Regionally Connected Reserve Network in a Changing and Uncertain World - DANIEL SPRING; JIRI BAUM; RALPH MAC NALLY; MICHAEL MACKENZIE; A. SANCHEZ‐AZOFEIFA; JAMES R. THOMSON (Conservation Biology, 2010)
Habitat connectivity is required at large spatial scales to facilitate movement of biota in response to climatic changes and to maintain viable populations of wide‐ranging species. Nevertheless, it may require decades to acquire habitat linkages at such scales, and areas that could provide linkages are often developed before they can be reserved. Reserve scheduling methods usually consider only current threats, but threats change over time as development spreads and reaches presently secure areas. We investigated the importance of considering future threats when implementing projects to maintain habitat connectivity at a regional scale. To do so, we compared forward‐looking scheduling strategies with strategies that consider only current threats. The strategies were applied to a Costa Rican case study, where many reserves face imminent isolation and other reserves will probably become isolated in the more distant future. We evaluated strategies in terms of two landscape‐scale connectivity metrics, a pure connectivity metric and a metric of connected habitat diversity. Those strategies that considered only current threats were unreliable because they often failed to complete planned habitat linkage projects. The most reliable and effective strategies considered the future spread of development and its impact on the likelihood of completing planned habitat linkage projects. Our analyses highlight the critical need to consider future threats when building connected reserve networks over time .